Instructional Media and English: Using Macromedia Flash to Teach EFL Writing - Ponimin Ponimin; Hilma Suryani (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2019)
The objectives of this study were to find out whether or not (1) Macromedia Flash enhanced students’ writing competence, and (2) there was significant difference between the students taught by using Macromedia Flash and those who were not. This study employed quasi experimental design, pretest and posttest nonequivalent groups. There were 39 students of one of junior high schools in Jambi participating in this study. They were grouped in two different classes. The experimental group consisted of 20 students while the other 19 students were in control group. The data were collected by using writing test. Students’ paragraphs writing scores in pretest and posttest were analyzed through the use of paired sample and independent sample t-test statistical analysis. The findings showed that first, based on the result of paired sample t-test, there was significant improvement of the students’ writing competence after the intervention. Second, with regard to the result of independent sample t test, there was significant difference of students’ writing competence in experimental group and control group.